Linguistic delving into the topic At Al-Maqri in the Meccan masterpiece (Journal of the College of Basic Education, 2022)
This research deals with the impact of linguistic evidence on semantic issues in the Meccan masterpiece book "by Abu al-Abbas Shihab al-Din Ahmad al-Maqri al-Maqri al-Maghribi al-Maliki (d. Active and effective) and other semantic topics.